2021
DOI: 10.1097/cm9.0000000000001720
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prognosis of optimal medical therapy after percutaneous coronary intervention in patients with coronary heart disease

Abstract: To the Editor: Revascularization, regardless of whether it is percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG), is still the dominant treatment of severe coronary heart disease (CHD). The long-term clinical outcome of revascularization is unpredictable because of the progression of atherosclerosis continuing after surgery. [1] Many studies and trials have proven that optimal medical therapy (OMT) with or without revascularization is critical for decreasing the incidence of adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Clinical trial and registry data have demonstrated a 31–39% and 21–32% prevalence of two-vessel and three-vessel diseases, respectively, in patients undergoing revascularization. [ 1 2 3 ] Multi-vessel coronary artery disease (CAD) occurs in 40–50% of patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI). [ 4 5 6 ] Previous studies have shown that complete revascularization is associated with lower rates of long-term adverse events when compared with incomplete revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trial and registry data have demonstrated a 31–39% and 21–32% prevalence of two-vessel and three-vessel diseases, respectively, in patients undergoing revascularization. [ 1 2 3 ] Multi-vessel coronary artery disease (CAD) occurs in 40–50% of patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI). [ 4 5 6 ] Previous studies have shown that complete revascularization is associated with lower rates of long-term adverse events when compared with incomplete revascularization.…”
Section: Introductionmentioning
confidence: 99%
“…At present, optimal medical therapy (OMT) [ 1 ] and timely coronary revascularization [ 2 ] continue to improve the prognosis of coronary heart disease (CHD) patients. However, angina pectoris, myocardial infarction, malignant arrhythmia, heart failure, and mortality remain high due to coronary artery stenosis or occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery bypass grafting (CABG) is one of the most effective treatments for coronary artery disease (CAD) patients. [1][2][3][4][5] CABG patients remain at a high risk for experiencing long-term events, with reported 10-year rates for major cardiovascular events ranging from 26.1% to 47.6%. [6][7][8][9][10][11] While several preoperative cross-tools are available that help physicians to evaluate surgical efficacy and tailor treatment over time.…”
Section: Introductionmentioning
confidence: 99%